2010
DOI: 10.1159/000313503
|View full text |Cite
|
Sign up to set email alerts
|

Pleural Granuloma Mimicking Malignancy 42 Years after Slurry Talc Injection for Primary Spontaneous Pneumothorax

Abstract: Background: Talc poudrage is considered a safe pleurodesis technique to improve the results of video-assisted thoracoscopic surgery in cases of primary spontaneous pneumothorax (PSP). Methods: We report the case of a patient with left pleural pseudo-nodular plaque and a high metabolic rate upon PET scan suspected for malignancy, occurring 42 years after slurry talc injection for conservative treatment of PSP. The patient presented with coughing, chest pain and weight loss. Thoracotomy was required to obtain a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…There are some large series with significant number of patients in past however those studies include PET only estimation however it is important to determine recent PET/CT scanners' results. As an example talc pleurodesis is another important reason of false positive FDG uptake in pleural plaques that can be discriminated by means of correlation with CT appearance (21,22). Additionally this study has superiority of having CT scan comparison with estimation of a different observer and advantage of the same time study for PET/CT and CT.…”
Section: Discussionmentioning
confidence: 87%
“…There are some large series with significant number of patients in past however those studies include PET only estimation however it is important to determine recent PET/CT scanners' results. As an example talc pleurodesis is another important reason of false positive FDG uptake in pleural plaques that can be discriminated by means of correlation with CT appearance (21,22). Additionally this study has superiority of having CT scan comparison with estimation of a different observer and advantage of the same time study for PET/CT and CT.…”
Section: Discussionmentioning
confidence: 87%
“…The granulomas may arise many years after the initial trauma or procedure in the form of tumor-like soft-tissue masses [26][27][28]. Multiple studies have indicated that lesions of active inflammation and infection may have higher 18 FDG activity on DTPI, similar to that in malignant lesions, thus resulting in suboptimal diagnostic performance of DTPI [29][30][31].…”
Section: Resultsmentioning
confidence: 99%
“…Acute events have been reported following pleurodesis including: fever, chest pain, hypoxemia, dyspnea, hypotension, lipothymia and less commonly hypercalcemia along with acute respiratory distress syndrome ( 25 ). As well, chronic events have also been reported including granulomas, pleural thickening, mesotheliod reaction and pulmonary nodules ( 6 8 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, most studies on humans have focused on assessing the clinical outcome exclusively, therein reporting only on short-term complications (often in severely symptomatic patients from a respiratory disease) while investigations on long-term complications have been few and mostly describing single cases ( 6 8 ). Limited available data on possible long term complications associated with talc pleurodesis are available in the Literature ( 2 , 3 , 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%